Alternative Medicine-Seeking Behavior among Cancer Patients at The Indonesian Cancer Foundation - Annisa Nur Illahi; Lucia Yovita Hendrati (Universitas Airlangga, 2021)
Background: A large proportion of cancer deaths are caused by patient delay in accessing hospital treatment. One of the causes of such delays is the use of alternative medicine. Purpose: This research is conducted to determine the characteristics and factors related to the behavior of seeking treatment in the form of alternative medicine among cancer patients at the Indonesian Cancer Foundation (Yayasan Kanker Indonesia). Methods: This research is a quantitative descriptive research with a cross-sectional study design. The target of the research is all patients who temporarily stayed at the Yayasan Kanker Indonesia from February–April 2020, a total of 45 patients aged ≥ 17 years who had been diagnosed with cancer. The data was obtained via questionnaires and interviews. The variables examined are the predisposition factors (sex, age, education, occupation, stage of cancer, time ranges for accessing health services after symptom onset, prior illness, family history), enabling factors (distance to health services, income, health insurance), and reinforcing factors (family support and information resources). Analysis of research data was conducted using frequency tables and Chi-Square or Fisher's Exact test. Results: The factors related to the behavior of seeking treatment via alternative medicine in cancer patients at Yayasan Kanker Indonesia are the stage of cancer (p=0.04), the time span between symptom onset and checking into health services (p=0.02), and length of illness (p=0.03). Conclusion: Alternative treatment search behavior is influenced by several factors, namely the stage of cancer, the time span between symptom onset and checking into health services, and the length of illness.